2021
DOI: 10.3390/cancers13081863
|View full text |Cite
|
Sign up to set email alerts
|

Nonreplicating Adenoviral Vectors: Improving Tropism and Delivery of Cancer Gene Therapy

Abstract: Recent preclinical and clinical studies have used viral vectors in gene therapy research, especially nonreplicating adenovirus encoding strategic therapeutic genes for cancer treatment. Adenoviruses were the first DNA viruses to go into therapeutic development, mainly due to well-known biological features: stability in vivo, ease of manufacture, and efficient gene delivery to dividing and nondividing cells. However, there are some limitations for gene therapy using adenoviral vectors, such as nonspecific trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 198 publications
0
4
0
Order By: Relevance
“…Most adenoviruses use the Coxsackie Adenovirus receptor (CAR) to infect cells, but some species (HAdV-B) enter the cell through binding to the complement regulatory protein CD46, which is ubiquitously expressed on many cancer cells [ 20 ]. Studies in animal models and clinical trials have demonstrated efficient infection and replication in lung mesothelioma, lung carcinoma, ovarian epithelial-like tumours, adenosquamous carcinoma, head and neck squamous cell carcinoma, colon carcinoma, colorectal adenocarcinoma, gastric adenocarcinoma, prostate carcinoma, pancreatic adenocarcinoma, melanoma, fibrosarcoma cells, glioblastoma, hepatocarcinoma cells, leukemic monocytes/macrophages [ 21 , 22 ]. Last generation helper-dependent adenovirus vectors (HDAds), also called “gutless” or fully deleted vectors, containing only inverted terminal repeats and the genome pack-aging signal, allow up to 36 kb insertions.…”
Section: Viral Vector Platforms For Cancer Therapymentioning
confidence: 99%
“…Most adenoviruses use the Coxsackie Adenovirus receptor (CAR) to infect cells, but some species (HAdV-B) enter the cell through binding to the complement regulatory protein CD46, which is ubiquitously expressed on many cancer cells [ 20 ]. Studies in animal models and clinical trials have demonstrated efficient infection and replication in lung mesothelioma, lung carcinoma, ovarian epithelial-like tumours, adenosquamous carcinoma, head and neck squamous cell carcinoma, colon carcinoma, colorectal adenocarcinoma, gastric adenocarcinoma, prostate carcinoma, pancreatic adenocarcinoma, melanoma, fibrosarcoma cells, glioblastoma, hepatocarcinoma cells, leukemic monocytes/macrophages [ 21 , 22 ]. Last generation helper-dependent adenovirus vectors (HDAds), also called “gutless” or fully deleted vectors, containing only inverted terminal repeats and the genome pack-aging signal, allow up to 36 kb insertions.…”
Section: Viral Vector Platforms For Cancer Therapymentioning
confidence: 99%
“…As mentioned above, the induction of ICD is essential for the success of oncolytic approaches, bringing into question the importance of virus replication to achieve this goal. Many approaches are being developed for the induction of oncolysis even when the virus, such as adenovirus, does not replicate ( Tessarollo et al, 2021 ). Our research has focused on the use of non-replicating adenoviral vectors for the transfer of genes intended to induce both cell death and immune activation including reversal of the immunosuppressive TME.…”
Section: Using Engineered Viruses For Cancer Immunotherapymentioning
confidence: 99%
“…Together, these studies show that our gene transfer approach is a promising immunotherapy for melanoma ( Hunger et al, 2017 ; Medrano et al, 2017 ; Cerqueira et al, 2020 ). The use of non-replicating vectors may be an advantage for our approach since the delivery of IFNβ can be counterproductive for replicating OVs ( Cerqueira et al, 2020 ; Geoffroy and Bourgeois-Daigneault, 2020 ; Tessarollo et al, 2021 ). The results to date are encouraging and research will continue, with critical development using clinically relevant models, such as testing with patient-derived tumor samples, including PDO and immunological ex vivo models ( Strauss et al, 2018 ).…”
Section: Using Engineered Viruses For Cancer Immunotherapymentioning
confidence: 99%
“…It is, therefore, possible that the risk of VITT is a common feature of drugs that use adenoviral vectors. It is important at this point to emphasize that adenoviral vectors are presently employed not only for vaccines against SARS-CoV-2 and EBOLA, 8 but they are under investigation for vaccines against other infectious diseases, 8 for cancer immunotherapy 9 and for gene therapy of inherited disorders. 10 Should it be shown that the risk of VITT is intrinsic to different adenovirus-based treatments, the risk-benefit ratio would be completely different if this approach is used to treat cancer or to prevent an infectious disease that has a mortality of about 1-2% (and in some age groups very close to 0%).…”
mentioning
confidence: 99%